The Effect of Serving "Breakfast After-the-Bell" Meals on School Absenteeism: Comparing Results From Regression Discontinuity Designs. (June 2021) - Kirksey, J. Jacob; Gottfried, Michael A.
With the rise in the availability of absenteeism data, it is clear that students are missing a staggering amount of school. Policymakers have focused efforts on identifying school programs that might reduce absenteeism. This study examined whether implementing the program "Breakfast After-the-Bell" (BAB) might reduce school absenteeism. Exploring longitudinal statewide datasets (Colorado and Nevada) containing school breakfast information linked to national data on chronic absenteeism rates, we used sharp and fuzzy regression discontinuity designs to examine the effects of BAB. Our findings suggest that schools serving BAB experienced declines in chronic absenteeism. The strongest effects were experienced by high schools, schools with higher rates of breakfast participation, schools serving universally free meals, and suburban schools. Implications are discussed.